Ebersole and Hess' gerontological nursing and healthy aging - Touhy, Theris A.; Jett, Kathleen (Missouri : Elsevier Science, 2018)
This text is intended to tell the story of both health and the health challenges we face as we age. A holistic approach, addressing body, mind, and spirit along a continuum of wellness, and grounded in caring and respect for the person, provides the framework for the text. It is designed to provide nurses, faculty, and students with the key information needed to promote healthy aging.
Section 1 : Foundations of healthy aging -- 1. Introduction to healthy aging -- 2. Cross-Cultural caring and aging -- 3. Biological theories of aging and age-related physical changes -- 4. Psychosocial, spiritual, and cognitive aspects of aging section -- Section 2 : Foundations of gerontological nursing -- 5. Gerontological nursing and promotion of healthy aging -- 6. Gerontological nursing across the continuum of care -- 7. Economic and legal issues -- Section 3: Fundamentals of caring -- 8. Assessment and documentation for optimal care -- 9. Safe medication use -- 10. Nutrition -- 11. Hydration and oral care -- 12. Elimination -- 13. Rest, sleep, and activity -- 14. Promoting healthy skin -- 15. Falls and fall risk reduction -- 16. Promoting safety -- Section 4: Promoting health in chronic illness -- 17. Living with chronic illness -- 18. Pain and comfort -- 19. Diseases affecting vision and hearing -- 20. Metabolic disorders -- 21. Bone and joint problems -- 22. Cardiovascular and respiratory disorders -- 23. Neurological disorders -- 24. Mental health -- Section 5 : Caring for elders and their caregivers -- 25. Care of individuals with neurocognitive disorders -- 26. Relationships, roles, and transitions -- 27. Caregiving -- 28. Loss, death, and palliative care
Includes bibliographical references and index.
Keywords: NURSING CARE